Fables. [07], Arabian nights (and days) - Willingham, Bill (Fables, 2006)
Now that they know the identity of the Adversary, Fabletown prepares to defend itself. That means forming alliances with others who are unconquered by the Adversary's legions, but the arrival of a delegations from the Arabian Homelands shows them how tricky this can prove to be.